Mesoarchaean-Palaeoproterozoic stratigraphic record of the Singhbhum crustal province, Eastern India: A synthesis - Mazumder, R.; Van Loon, A.; Mallik, L.; Reddy, Steven; Arima, M.; Altermann, W.; Eriksson, P.; De, S. (2012)
The Mesoarchaean–Palaeoproterozoic stratigraphic record of the Singhbhum crustal province, eastern India, implies sedimentation and volcanism in a changing tectonic scenario, and thus assumes immense geological significance. Although efforts have been made by many researchers in the past several decades to summarize various geological aspects of the Singhbhum crustal province, a critical synthesis of various stratigraphic issues was long overdue. The present contribution is an updated critical synthesis of the Mesoarchaean–Palaeoproterozoic stratigraphic record of the Singhbhum crustal province. We have pointed out the problematic stratigraphic issues of the Singhbhum crustal province that deserve careful scrutiny in order to gain better insights into the mode of stratigraphic sequence building.